2017
DOI: 10.11648/j.ijae.20170203.15
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Levels and Intensity of Adoption of New Rice for Africa (Nerica) Among Rice Farmers in Ogun State, Nigeria

Abstract: Abstract:The study determined the levels of New Rice for Africa (NERICA) technology adoption and identified the factors influencing the levels and intensity of technology adoption among the NERICA rice farmers with a view to improving NERICA production among rice farmers in the study area. A multi-stage sampling technique was used to select 200 NERICA rice farmers for the study. Primary data collected were analyzed using descriptive statistics and technology adoption index. Results showed that there were two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…The result indicates that the older the farmer the lesser the acceptance of NERICA 1 rice because older people are less energetic and have more farming experience which could make them reject new technologies and stick to traditional ways of farming practices. The result concurs with Ogunya et al (2017) who reported that the age of farmers was found to be significant and negatively related to the level of NERICA rice adoption.…”
Section: Factors Influencing Acceptance Of Nerica 1 Ricesupporting
confidence: 91%
“…The result indicates that the older the farmer the lesser the acceptance of NERICA 1 rice because older people are less energetic and have more farming experience which could make them reject new technologies and stick to traditional ways of farming practices. The result concurs with Ogunya et al (2017) who reported that the age of farmers was found to be significant and negatively related to the level of NERICA rice adoption.…”
Section: Factors Influencing Acceptance Of Nerica 1 Ricesupporting
confidence: 91%
“…Many scholars such as Mulugeta [14], Wuletaw and Daniel [15], Ogunya et al [16], and Julius and Jimoh [17] had given weight to each package to obtain the intensity of adoption of a given technology. erefore, this study has given different weights for each package of Tef production technology (see equation (2).…”
Section: Status Of Adoption Of Tef Technology Packagesmentioning
confidence: 99%
“…Wuletaw and Daniel [15] give a proportion score to calculate the adoption intensity of Malt-barley. Research conducted by Ogunya et al [16] used weight for each package to calculate the adoption intensity and level of Nerica rice varieties in Ogun, Nigeria. Julius and Jimoh [17] give weight for each technology packages to calculate the intensity of adoption of cocoa production technology packages in Ekiti State, Nigeria.…”
Section: Status Of Adoption Of Tef Technology Packagesmentioning
confidence: 99%